Flavonoid Group of Smilax glabra Roxb. Regulates the Anti-Tumor Immune Response Through the STAT3/HIF-1 Signaling Pathway - Guo, Yingxue; Mao, Weiye; Jin, Lu; Xia, Linying; Huang, Jie; Liu, Xia; Ni, Ping; Shou, Qiyang; Fu, Huiying (Frontiers in Pharmacology, 2022)
Background:Smilax glabra Roxb. (SGR) is a widely used traditional Chinese medicine, which has known effects of enhancing immunity. However, its anti-tumor effects and mechanism of action are still unclear. Methods: We selected MMTV-PyMT mice to determine the anti-tumor efficacy of SGR ethyl acetate (SGR-EA). First, flow cytometry was used to detect the number of immune cells in the mice tumor microenvironment. Furthermore, M2 polarization of macrophages was stimulated in vitro, and the expressions of macrophage M1/M2 surface markers and mRNA were as determined. Finally, we carried out a network pharmacology analysis on the active components of SGR-EA and in vitro experiments to verify that SGR-EA regulated the hypoxia-inducible factor (HIF)-1 signaling pathway to modulate the anti-tumor immune response by resetting M2 macrophages toward the M1 phenotype which inhibited tumor growth and lung metastasis in the mice. Result: SGR-EA inhibited tumor growth and lung metastasis in the mice. Tumor-associated macrophages switched from M2 to the tumor-killing M1 phenotype and promoted the recruitment of CD4+ and CD8+ T cells in the tumor microenvironment. In vitro, SGR-EA significantly inhibited the polarization of macrophages into M2 macrophages and increased the number of M1 macrophages. In addition, following an intervention with SGR-EA, the expression of the HIF-1 signaling pathway-related proteins stimulated by interleukin-4 in macrophages was significantly inhibited. Conclusion: SGR-EA played an anti-tumor role by inhibiting the activation of the HIF-1 signaling pathway and response by resetting tumor-associated macrophages toward the M1 phenotype.